Is the spiral morphology of the Elias 2-27 circumstellar disc due to gravitational instability?. Issue 1 (28th February 2018) - Hall, Cassandra; Rice, Ken; Dipierro, Giovanni; Forgan, Duncan; Harries, Tim; Alexander, Richard
Abstract: A recent Atacama Large Millimeter/submillimeter Array (ALMA) observation of the Elias 2-27 system revealed a two-armed structure extending out to ∼300 au in radius. The protostellar disc surrounding the central star is unusually massive, raising the possibility that the system is gravitationally unstable. Recent work has shown that the observed morphology of the system can be explained by disc self-gravity, so we examine the physical properties of the disc necessary to detect self-gravitating spiral waves. Using three-dimensional smoothed particle hydrodynamics, coupled with radiative transfer and synthetic ALMA imaging, we find that observable spiral structure can only be explained by self-gravity if the disc has a low opacity (and therefore efficient cooling), and is minimally supported by external irradiation. This corresponds to a very narrow region of parameter space, suggesting that, although it is possible for the spiral structure to be due to disc self-gravity, other explanations, such as an external perturbation, may be preferred.